Disputed territory, defensive alliances and conflict initiation. (April 2014) - Wright, Thorin M.; Rider, Toby J.
In this study, we evaluate the effects of alliance behavior on the probability of militarized conflict initiation with specific emphasis placed on the issues at stake in the conflict. After much debate over the relationship between alliances and conflict, recent research suggests that specific types of alliances, namely defensive pacts for target states, decrease the likelihood that potential challengers will initiate militarized disputes. Revisiting the alliance–conflict relationship, we allow the type of issue at stake to vary in order to determine whether this deterrent effect holds even when the most salient of issues are under contention. Specifically, we introduce indicators for whether the two states are competing over territorial issues, a high-salience stake that is particularly conflict-prone. Using a number of different indicators for territorial competition and examining several different time periods, analyses suggest that targeted defensive alliances do indeed have a deterrent effect against named adversaries, even when the most salient of issues are at stake.